Оказіональні лексичні новотвори в мові прози Михайла Стельмаха - Ткаченко, Тетяна; Tkachenko, Tatiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено лінгвостилістичний аналіз оказіоналізмів, зафіксованих у художніх текстах прози Михайла Стельмаха. Визначено структуру, семантику, частиномовну належність оказіональних утворень, встановлено найбільш продуктивні способи оказіонального словотворення в мові прози письменника. З’ясовано стилістичний потенціал індивідуально-авторських новотворів та особливості їх використання з метою стилізації розмовності та оновлення й збагачення образних ресурсів художніх творів письменника. In the article the linguo-stylistic analysis, clucked in the fiction prose texts of Mykhailo Stel’makh is implemented. Here one can see the defined structure, semantics, the fixed reference of the language definition formation of the occasional type, the classified most productive ways of the word-building of the occasional type in the author’s prose language. This article also contains the out view of the stylistic potential of the individual and author’s neologisms and the peculiarities of their use when styling the colloquial style speech and refreshing and enriching the image resources of the author’s works.
Occasional lexical neologisms in the language of prose Michael Stelmaha
Keywords: оказіоналізм; потенційне слово; новотвір; індивідуальне словотворення; розмовність; occasionalism; potential word; neologism; individual wordformation; colloquial style speech